Des normes procréatives sécularisées ? L’opposition catholique française à l’ouverture de la PMA aux couples de femmes et aux femmes seules - Séverine Mathieu (Enfances, Familles, Générations, 2021)
Research framework: In the most recent revision of the French bioethics laws (2018-2019), the Catholic Church has been very active in regards to a most controversial issue that is the access to ART for lesbian couples and single women. Objectives: This article explores how the Catholic procreative norms, which are considered by the magisterium as the way of becoming a parent, are translated in a secular argument. Methodology: Drawing on an ethnographic survey of public debates that preceded and accompanied the present revision of the bioethics law, this article is using two types of data. On the one hand, observations were made during the “États généraux de la bioéthique” that were held between January and May 2018 and, on the other hand, an analysis of the proposals was undertaken by means of their website. Interventions in the media and documents produced by the Catholic Church were also compiled and analyzed. Results: The Roman Magisterium seeks to show that its recommendations in respect to family matters are not based on faith but rather on the correct understanding of nature’s mechanisms. To enforce its discourse, the Church employs a rhetoric invoking the secular library. Conclusions: In this context, the French Catholic mobilization against access to ART for lesbian couples and single women is trying to prevent a law change by referring to so-called traditional values and defending them in the name of secular principles. This can be interpreted as the expression of an “ostensible” (Hervieu-Léger, 2017), in which Catholic norms no longer permeate reproductive rights. Contribution: By endeavouring to impose its procreative norms as well as its condemnation of contraception and abortion, the French Catholic Church resorts to secular norms which demonstrates the secularization of Catholicism.